(untitled) - Carson, Nacie (San Francisco, 2012)
As Darwin famously observed, the beaks of each generation of Galapagos Island finches change to accommodate shifting food resources, allowing the birds to survive by adapting their capabilities to the new environment. Today's business people should take note: In the post-crisis economy, traditional career strategies spell professional extinction, but the fluid new "gig economy" offers tremendous potential for anyone willing to adapt. Based on her popular blog and drawing on her leadership development experience, Nacie Carson explains what it takes to make it in today's world of work.
Keywords: Career development.,Thành công trong kinh doanh,Phát triển sự nghiệp,Success in business